A dynamically clock-controlled binary stream cipher with memory and dynamic multiplexing "the mono stream cipher" - Uzun, Orçun. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
Streams ciphers are appropriate for high speed encrypted communications because this type of ciphers provide high output speed and ease of implementation in hardware. Generally, stream ciphers makes use of Linear Feedback Shift Registers (LFSRs) due to its simplicity and its ease of realization both in software and hardware. However, this efficient component is not sufficient when we consider security. The designer should use many nonlinear functions and mechanisms to make the system more resistant against cryptanalysis. A stream cipher should have high period, high linear complexity, good statistical properties and be resistant against most recent successful attacks such as algebraic attacks, correlation attacks, time memory tradeoff attacks, and divide and conquer attacks. In this thesis, a new stream cipher design is proposed. MONO is designed to be resistant against algebraic and correlation attacks. In the design phase, the objective was to design a stream cipher with good randomness, high period and linear complexity and resistance against many attacks. The other objective was to design a realizable stream cipher. Also the innovation in this thesis is the proposal of a dynamically clock controlled filter generator with the use of memory and dynamic multiplexing. The initialization step of MONO is based on solving a mathematical problem which is known to be difficult, to deduce the secret key. It is showed that MONO stream cipher satisfies high period and linear complexity. Also, system has good statistical properties. We have made several statistical tests to see whether MONO cipher satisfies basic requirements for random number generation. MONO passed all of the tests. MONO is secure against many important attacks such as correlation attacks, algebraic attacks, divide and conquer attacks, and time memory trade off attacks. The hardware implementation of MONO has also been investigated and we had observed appropriate results. Consequently, we can say that MONO is appropriate for both hardware and software applications.
Keywords: Ciphers.; Cryptography.